2022
DOI: 10.3390/bioengineering9110615
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Fire with Fire: Exosomes and Acute Pancreatitis-Associated Acute Lung Injury

Abstract: Acute pancreatitis (AP) is a prevalent clinical condition of the digestive system, with a growing frequency each year. Approximately 20% of patients suffer from severe acute pancreatitis (SAP) with local consequences and multi-organ failure, putting a significant strain on patients’ health insurance. According to reports, the lungs are particularly susceptible to SAP. Acute respiratory distress syndrome, a severe type of acute lung injury (ALI), is the primary cause of mortality among AP patients. Controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 228 publications
0
2
0
Order By: Relevance
“…In a previously published review, we elucidated the ambivalent function of exosome-specific miRNAs in acute pancreatitis, which can be likened to a double-edged sword. 6 Following the onset of SAP, it has been observed that inflammatory cells, including macrophages and neutrophils, can release exosome-specific inflammatory miRNAs. This release can damage the pancreas and exacerbate dysfunction in extrapancreatic organs such as the intestine and lungs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previously published review, we elucidated the ambivalent function of exosome-specific miRNAs in acute pancreatitis, which can be likened to a double-edged sword. 6 Following the onset of SAP, it has been observed that inflammatory cells, including macrophages and neutrophils, can release exosome-specific inflammatory miRNAs. This release can damage the pancreas and exacerbate dysfunction in extrapancreatic organs such as the intestine and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Exo-specific miRNAs obtained from serum, plasma, and ascites significantly impact the onset and progression of SAP by modulating posttranscriptional modification and inflammatory cell signaling Exo-specific miRNAs also have the potential to serve as diagnostic markers and therapeutic agents for SAP. 6 Emodin (EMO) is an anthraquinone derivative that is abundantly present in Rheum palmatum L., Polygonum multiflorum Thunb., and Polygonum cuspidatum Siebold & Zucc. 7 The solubility characteristics of EMO indicate that it is soluble in alcohol and alkali solutions while exhibiting almost negligible solubility in water.…”
Section: Introductionmentioning
confidence: 99%
“…Search terms #1 TS = ("Pancreatitis" OR "Pancreatitis, Acute Edematous" OR "Acute Edematous Pancreatitides" OR "Edematous Pancreatitides, Acute" OR "Edematous Pancreatitis, Acute" OR "Pancreatitides, Acute Edematous" OR "Acute Edematous Pancreatitis" OR "Pancreatic Parenchymal Edema" OR "Edema, Pancreatic Parenchymal" OR "Pancreatic Parenchymal Edemas" OR "Parenchymal Edema, Pancreatic" OR "Pancreatic Parenchyma with Edema" OR "Pancreatitis, Acute" OR "Acute Pancreatitis" OR "Acute Pancreatitides" OR "Pancreatitides, Acute" OR "Peripancreatic Fat Necrosis" OR "Fat Necrosis, Peripancreatic" OR "Necrosis, Peripancreatic Fat" OR "Peripancreatic Fat Necroses") #2 TS = ("Non-coding RNA" OR "microRNA" OR "microRNAs" OR "Circular RNA" OR "Circular RNAs" OR "long non-coding RNA" OR "long non-coding RNA" OR "lncRNA" OR "lncRNAs" OR "Small interfering RNA" OR "SiRNA" OR "Piwi-interacting RNA" OR "small nucleolar RNA" OR "ribosomal RNA" OR "transfer RNA" OR "small nuclear RNA" OR "tRNA-Derived Fragments" OR "tRNA halves" OR "miRNA" OR "circRNA" OR "tiRNA" OR "tRF" OR "miRNAs" OR "circRNAs" OR "miR*" OR "lnc*" OR "circ_*") #3 #1 AND #2 authors is not too close. A total of 15,478 authors were included among the co-cited authors in this research area, and 30 of them were cited more than 30 times in total, with Masamune Atsushi (98) having the most, followed by Anna E Szafranska (68), and David P Bartel (66). The view analysis of these 30 authors using VOSviewer software was divided into 3 clusters, as shown in Figure 4B, represented by 3 colors, Masamune, Atsushi and Minoti V Apte as the central blue cluster, Anna S Gukovskaya, Bhatia M and Banks PA as the central red cluster, Anna E Szafranska, Bartel DP, and Bloomston M were centered in the green cluster.…”
Section: Itemmentioning
confidence: 99%
“…The latest keywords to break out in the last 2 years are injury, pathway, and extracellular vesicles, all closely related to non-coding RNAs. The topic of injury has also been mentioned in studies of acute pancreatitis, and acute pancreatitis-associated pulmonary and intestinal injuries have had a large number of correlative studies in recent years, [65][66][67] It is well illustrated that acute pancreatitis causes multi-organ functional impairment and interacts with each other. Extracellular vehicles (EVs) are generated by cells carrying proteins and nucleic acids that regulate the host immune response by mediating the transfer of intercellular substances and, therefore, play a significant role in the development and progression of inflammatory diseases, [68] and miRNAs have been extensively examined as a key component of EVs in order to investigate their roles in AP development, [69] in addition EVs have other functions that affect acute pancreatitis.…”
Section: Research Hotspots and Frontiersmentioning
confidence: 99%
“…The lungs are particularly susceptible to the effects of severe acute pancreatitis, with the development of ALI being a significant concern [15]. Studies have explored different interventions to mitigate the impact of acute pancreatitis on the lungs.…”
Section: Introductionmentioning
confidence: 99%